Improving municipal management for cities to succeed : (The World Bank, 2009)
Cities now house half the world s population and produce 70 percent of its GDP. Managing them well helps development. Strengthening municipal management of planning, finance, and service provision has been at the core of World Bank support through municipal development projects (MDPs). This book reviews how, worldwide, nearly 3,000 municipalities have benefitted from 190 World Bank-supported MDPs over the past decade, three quarters of which achieved satisfactory outcomes. The finance dimension of MDPs computerized accounting, revenue generation, and municipal credit produced some of the best results, but weaker outcomes came from attempts to stimulate private finance of municipal services.City planning, used by municipalities worldwide, was not a strong priority for MDPs. But building municipal information systems, for example in Chile, were successful. Monitoring and evaluation rarely worked well, except when municipalities themselves were convinced of its usefulness, such as in Russia, Tunisia, and Colombia. Results in managing service provision were mixed. The poverty focus of MDPs was strikingly weak across the portfolio. Cost-benefit analysis rarely prioritized municipal investments. But MDPs helped municipalities strengthen their procurement function.MDPs helped municipalities manage services more effectively. Better results still can come from a stronger poverty focus, more attention to planning and prioritizating investments, and more effective operation and maintenance of such investments.